The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1167/iovs.61.4.46
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Characteristics of the Optic Nerve Head and Choroidal Thickness in High Myopia

Abstract: This study aimed to explore the morphological characteristics of Bruch's membrane opening distance (BMOD), border length (BL), border tissue angle (BTA), vertical tilt angle, and peripapillary atrophy (PPA), as well as their associations with choroidal thickness (ChT) in young healthy highly myopic eyes. METHODS. A total of 167 patients with high myopia and 172 individuals without high myopia were enrolled. All of the subjects were divided by axial length. The PPA area was measured on fundus photographs. BMOD,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 48 publications
6
17
0
Order By: Relevance
“…In the correlation analyses, the results indicated that thinning of the mCHT was related to the PPA area and the degree of optic disc tilt, but not the OI. These results are consistent with the results of Chen 13 and Hu et al 29 Among people with HM, thinning of the mCHT may also be affected by changes in optic disc tilt and increased PPA area, aside from the effects of AL. We further found that decreasing macular CCVD and CCF area were related to increasing PPA area.…”
Section: Discussionsupporting
confidence: 92%
“…In the correlation analyses, the results indicated that thinning of the mCHT was related to the PPA area and the degree of optic disc tilt, but not the OI. These results are consistent with the results of Chen 13 and Hu et al 29 Among people with HM, thinning of the mCHT may also be affected by changes in optic disc tilt and increased PPA area, aside from the effects of AL. We further found that decreasing macular CCVD and CCF area were related to increasing PPA area.…”
Section: Discussionsupporting
confidence: 92%
“…All subjects have understood the study protocol and signed informed consent forms. The protocol was consistent with those of previous studies ( 20 , 21 ).…”
Section: Methodssupporting
confidence: 71%
“…The average thickness of all nine sectors was calculated in the macular region. While in the peripapillary area, only four regions of the outer ring were applied because no choroidal tissue was found in the central sector and the inner ring, and the topographic maps were not reliable in these regions ( 20 , 21 ).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, owing to the consistency in the measurement method used, the difference between the two groups should be reliable. Planimetric fundus photography was widely used in the measurement and analysis of PPA, ODO and ODA (Xu et al 2009;Kim et al 2019;Hu et al 2020); however, planimetric fundus photography analysis cannot reflect the spatial morphology; therefore, we hope that three-dimensional imaging technology will become available in the future to analyse the early changes in ODM and PPS around the disc affected by hyperglycaemia.…”
Section: Discussionmentioning
confidence: 99%
“… 2019 ; Hu et al. 2020 ); however, planimetric fundus photography analysis cannot reflect the spatial morphology; therefore, we hope that three‐dimensional imaging technology will become available in the future to analyse the early changes in ODM and PPS around the disc affected by hyperglycaemia.…”
Section: Discussionmentioning
confidence: 99%